New imaging algorithm for material damage localisation based on impedance measurements under noise influence - de Castro, Bruno Albuquerque [UNESP]; Baptista, Fabricio Guimarães [UNESP]; Ciampa, Francesco (Elsevier, 2020)
The electro-mechanical impedance (EMI) measurements have been extensively studied in recent years to provide a reliable diagnosis of aerospace infrastructures. Existing imaging algorithms for EMI-based damage localisation have been proposed for controlled inspection environments or under the sole influence of temperature variations. However, the presence of signal noise may alter impedance signals and limit the use of the EMI method in real operating scenarios. Based on this issue, this short communication proposes a novel EMI probabilistic imaging algorithm for damage localisation under noisy inspections. Furthermore, as another advantage compared to traditional techniques, which do not perform a noise compensation, the proposed application does not require high computational cost since it does not require licensed software or the calculation of acoustic parameters. Experimental results on an aluminium plate-like structure revealed that the new algorithm proved to be adequate to image the location of damage under noise influence as opposed to traditional approaches.
Keywords: CCSD; Damage localisation; Imaging algorithm; Impedance measurements; Probabilistic image; SHM; Signal processing